2008
DOI: 10.1101/gr.077578.108
|View full text |Cite
|
Sign up to set email alerts
|

In-depth characterization of the microRNA transcriptome in a leukemia progression model

Abstract: MicroRNAs (miRNAs) have been shown to play important roles in physiological as well as multiple malignant processes, including acute myeloid leukemia (AML). In an effort to gain further insight into the role of miRNAs in AML, we have applied the Illumina massively parallel sequencing platform to carry out an in-depth analysis of the miRNA transcriptome in a murine leukemia progression model. This model simulates the stepwise conversion of a myeloid progenitor cell by an engineered overexpression of the nucleop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
143
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(161 citation statements)
references
References 64 publications
16
143
0
2
Order By: Relevance
“…In-depth miRNA profiling by deep sequencing with high-resolution views of expressed miRNAs over a wide dynamic range of expression levels has already been realized in several kinds of tissues and cell types, including human embryonic stem cells (25), human B cells (26), cell types during mouse lymphopoiesis (17), human renal cell carcinoma (27), and mouse leukemia (28). The study that revealed dynamic miRNomes during lymphopoiesis selected mouse adherent lymphokine-activated NK cells (ALAK, NK cells) as a mouse NK cell substitute to get the mouse NK cell miRNome (17), which may affect the biological and physiological significance of this mouse NK cell miRNome.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth miRNA profiling by deep sequencing with high-resolution views of expressed miRNAs over a wide dynamic range of expression levels has already been realized in several kinds of tissues and cell types, including human embryonic stem cells (25), human B cells (26), cell types during mouse lymphopoiesis (17), human renal cell carcinoma (27), and mouse leukemia (28). The study that revealed dynamic miRNomes during lymphopoiesis selected mouse adherent lymphokine-activated NK cells (ALAK, NK cells) as a mouse NK cell substitute to get the mouse NK cell miRNome (17), which may affect the biological and physiological significance of this mouse NK cell miRNome.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence variations in mature miRNAs are referred to as isomiRs (11)(12)(13). IsomiRs may be produced by differential excision by DICER1, which can lead to variations in the 5′ and 3′ ends of the mature miRNA (14).…”
Section: Significancementioning
confidence: 99%
“…In mammals, high-throughput sequencing methods that have contributed to miRNA discovery efforts have included massively parallel signature sequencing (MPSS) (Mineno et al 2006), miRNA serial analysis of gene expression (miRAGE) (Cummins et al 2006), 454 pyrosequencing (Berezikov et al 2006a(Berezikov et al , 2007Calabrese et al 2007), and Illumina sequencing (Babiarz et al 2008;Kuchenbauer et al 2008). …”
mentioning
confidence: 99%